2018
DOI: 10.1136/gutjnl-2017-315690
|View full text |Cite
|
Sign up to set email alerts
|

Lysine methyltransferase 2D regulates pancreatic carcinogenesis through metabolic reprogramming

Abstract: ObjectiveDespite advances in the identification of epigenetic alterations in pancreatic cancer, their biological roles in the pathobiology of this dismal neoplasm remain elusive. Here, we aimed to characterise the functional significance of histone lysine methyltransferases (KMTs) and demethylases (KDMs) in pancreatic tumourigenesis.DesignDNA methylation sequencing and gene expression microarrays were employed to investigate CpG methylation and expression patterns of KMTs and KDMs in pancreatic cancer tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 38 publications
4
62
1
Order By: Relevance
“…The publically available CRISPR screening platform, Achilles (65), suggests a dependency of KMT2D mutant melanomas on specific genes in these other metabolic pathways which need further exploration. Indeed, a recent study suggested enhanced fatty acid metabolism in pancreatic cancer (53). Interestingly, the dependence of SMARCA4 mutant cancers on the blockade of oxidative phosphorylation was recently demonstrated (66) in lung cancer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The publically available CRISPR screening platform, Achilles (65), suggests a dependency of KMT2D mutant melanomas on specific genes in these other metabolic pathways which need further exploration. Indeed, a recent study suggested enhanced fatty acid metabolism in pancreatic cancer (53). Interestingly, the dependence of SMARCA4 mutant cancers on the blockade of oxidative phosphorylation was recently demonstrated (66) in lung cancer.…”
Section: Discussionmentioning
confidence: 97%
“…We observed that ~15% of melanoma cases identified harbored missense mutations in KMT2D whereas ~5%-8% of patients harbored missense mutations in KAT4 (Figures 2B and S2A) (35). As KMT2D mutations are prevalent (36-52) and this gene is increasingly reported to be a potential tumor suppressor across other tumor types (4)(5)(6)(7)36,53), we next sought to deeply characterize the mechanism of action of KMT2D in melanoma, particularly as the strongest phenotype in RNAi screen was seen with the KMT2D loss. A subset of the missense mutations in KMT2D were truncating or frameshift insertions/deletions (4.4%) that likely abrogates histone methyltransferase activity ( Figure 2B).…”
Section: Gemm Model Confirms Kmt2d Is a Potent Tumor Suppressor In Mementioning
confidence: 99%
“…Dawkins and colleagues reported that reduced expression of KMT2D is associated with improved survival of PDAC patients 43 . However, a more recent study by Koutsioumpa and colleagues showed that low KMT2D expression increased proliferation and tumorigenicity in PDAC by altering glucose and lipid metabolism 44 . Our study showed that primary and metastatic PDACs had significantly lower expression of KMT2D and loss of KMT2D promoted PDAC invasion and migration, which supports a tumor-suppressive role of KMT2D in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide analysis was performed using publicly available H3K4me3 (GSE85886) and HOXA13 (GSE49402) dataset and HOTTIP binding analysis by Triplex Domain Finder to identify genes with HOTTIP and H3K4me3 but not HOXA13 enrichment at their promoters (Fig. 4A) [14][15][16]. As expected, HOTTIP targets CYB5R2, SULT1A1, KIF26A, SLC1A4 and TSC22D1 were insensitive to HOXA13 knockdown ( Fig.…”
Section: Genome-wide Identification Of Non-canonical Hottip-wdr5-mll1mentioning
confidence: 95%